Pseudo-amplitude scan sonar maps. - Kuc, R. (IEEE Transactions on robotics and automation)
This paper analyzes a novel sonar mapping procedure that displays the amplitude of the echoes using the conventional Polaroid 6500 ranging module. By resetting the module immediately after an echo indication is observed, the number of indications produced by the module is related to the echo amplitude. We then generate pseudo-amplitude scan (PAS) sonar maps that display more information than conventional maps. The ranging module operation is described and verified experimentally. The improved information content of PAS sonar maps is illustrated by scanning simple objects having different reflecting strengths. Artifacts resulting from interactions between objects are discussed